2019
DOI: 10.1126/sciadv.aay0044
|View full text |Cite
|
Sign up to set email alerts
|

FeSe quantum dots for in vivo multiphoton biomedical imaging

Abstract: FeSe quantum dots of multiphoton absorption were used to image tumor cells in deeper tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
40
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 44 publications
1
40
0
Order By: Relevance
“…subcutaneous tumors, and their presence in the tumor was revealed by TPE at 800 nm at a depth of up to 500 µm by a cyan color due to FeS QD fluorescence, [130]. Some FIBN such as FePt NP associated with NOPS fluorescent dye, which are non-fluorescent under SPE due to fluorescence quenching, can be made fluorescent under TPE and used for in vivo imaging, e.g.…”
Section: Detection Methods Of Fluorescent Iron-based Nanomaterialsmentioning
confidence: 99%
“…subcutaneous tumors, and their presence in the tumor was revealed by TPE at 800 nm at a depth of up to 500 µm by a cyan color due to FeS QD fluorescence, [130]. Some FIBN such as FePt NP associated with NOPS fluorescent dye, which are non-fluorescent under SPE due to fluorescence quenching, can be made fluorescent under TPE and used for in vivo imaging, e.g.…”
Section: Detection Methods Of Fluorescent Iron-based Nanomaterialsmentioning
confidence: 99%
“…Kwon et al conjugated iron selenide QDs with monoclonal human epidermal growth factor receptor 2 antibodies to study xenograft breast tumor model in mice. [56] The tracking and study of biomolecules labeled with QDs in vitro and in vivo is a reality in several areas, allowing us to analyze the location and distribution of bioconjugate in biological systems. Silva et al demonstrated that the CdSe/ CdS MSQDs could be bioconjugated with several biomolecules aiming at the most diverse luminescent probes [38][39][40][41][42] in biosensors.…”
Section: Nanocrystals As Luminescent Markers (Nanomarkers)mentioning
confidence: 99%
“…Since the discovery of superconductivity from iron compounds [1,2], iron-based semiconductors, particularly iron selenides, have attracted great interests from physicists and chemists [3][4][5][6][7][8][9][10]. Considerable research on iron selenides has been carried out not only to aim at high-temperature superconductivity but also various other novel applications [4,11].…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research on iron selenides has been carried out not only to aim at high-temperature superconductivity but also various other novel applications [4,11]. For instance, among the complex phase diagram, FeSe and FeSe 2 have been demonstrated as photo-absorbers for photovoltaics [12], anode materials for sodium-ion batteries [8,10], cathode materials for lithium-air batteries [5], and non-linear optical materials for bioimaging [9,13]. Recently, excellent electrocatalysis performance in oxygen evolution reaction (OER) [6,14], hydrogen evolution reaction (HER) [15][16][17], and overall water splitting [7,11] have also been discovered and demonstrated in FeSe 2 and FeSe.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation